The Role of Forensic Medicine in Modern Criminal Justice: A Review of Current Practices and Innovations - Balhareth , Abdullah Ali Saleh; jamesh, Mohammed; Zabarah, Ghanem Abdullah; Almotlaq, Mohammed Mohammed; alabaaltahin, Manae ali madran; Al Jaarah, Abdullah Hussain Ali; Aldawsari , Ali Ghannam Ali; Almastaneer, Khaled Ali Mohammed; Alyami, Saleh Mohammed; Al Yami , Abdullah Saleh Hamad (Journal of Ecohumanism, 2024)
Forensic medicine plays a pivotal role in modern criminal justice by providing scientific insights that aid in solving crimes, identifying victims, and ensuring the accurate administration of justice. This review examines the current practices in forensic medicine, including autopsies, toxicology, DNA analysis, and forensic anthropology, highlighting their applications in various criminal cases. Technological innovations, such as advanced DNA technologies, digital forensics, and forensic imaging, have significantly enhanced the field, improving accuracy and efficiency in investigations. The review also addresses challenges faced by forensic medicine, including issues of accuracy, resource constraints, and ethical considerations surrounding privacy and consent. The integration of artificial intelligence and portable forensic devices is explored as part of the ongoing evolution within the field. By analyzing the impact of these advancements on case resolutions, exonerations, and crime prevention, this article underscores the critical role of forensic medicine in the justice system and discusses future directions for research and practice. The insights presented aim to inform ongoing improvements in forensic methodologies and to foster a justice system that is both scientifically rigorous and ethically responsible.